Psychosocial Evaluation of Children Aged 3-6 Years After Circumcision - Emine Güneş Şan; Naime Altay (Galenos Publishing House, 2024)
Objective: Circumcision can be quite traumatic for children between the ages of 3 and 6 because of their cognitive, social, emotional, and psychological developmental characteristics. This study aimed to evaluate the psychosocial effects of circumcision at the age of 3-6. Method: This is a descriptive comparative study. The participants of the study consisted of 116 boys and their mothers (circumcised group, n=58; non-circumcised group, n=58). A "the descriptive characteristics form" and "psychosocial status evaluation scale-parents form for children 3-6 years of age" were used to collect data. Results: The mean "psychosocial status evaluation scale-parents form for 3-6 years old children" score of the non-circumcised group was 23.21±8.99, while the mean "psychosocial status evaluation scale-parents form for 3-6 years old children" score of the children in the circumcision group before circumcision was 23.21±12.18; this value was 28.17±14.34 after circumcision. There was a statistically significant difference (p<0.05) in the mean scores between the circumcised group before and after circumcision and between the mean scores of the circumcised and uncircumcised groups. Conclusion: Children aged 3-6 may experience psychosocial problems after circumcision. Therefore, it is recommended that circumcision should not be preferred unless there is a medical necessity in the 3-6-year-old age group and that the child should be psychologically prepared for the procedure when it is necessary.